A Price promotion trust and product quality factors in affecting interest in buying in online store - Nurul Azizah; Hendra Prasetya (Enrichment : Journal of Management, 2023)
The purpose of this study was to determine the impact of celebgrams. The study question is whether price, advertising, trust, and product quality have a partially significant effect on the economics student's interest in his online shop purchases at her Wijaya Kusuma University in Surabaya. The population consists of economics students at her Wijaya Kusuma University in Surabaya. Determining a sample using a targeted sampling method characterized by having purchased clothes from an online shop. Survey variables consist of his four independent variables, price, promotion, trust, and product quality, and one dependent variable, willingness to buy. Distribute surveys to collect data and process up to 100 respondents. The analysis method uses multiple regression analysis and the hypothesis test uses t-test. The results are as follows.1) Price positively influences purchase intent in online stores, but not by a large amount. (2) Advertising has a positive and significant effect on purchasing interest in online shops. (3) Trust has a large positive impact on purchase intentions in an online shop. (4) Product quality has a large positive impact on purchase intentions in online stores.